METODE DAN SKEMA PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL (PPHI) UNTUK MENINGKATKAN PRODUKTIVITAS SISTEM HUKUM KETENAGAKERJAAN - Ivan Iskandar; Anna Pratiwi; Tji Natalia Budiman; Hedi Ceril Saedi; Yeti Kurniati (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to analyze the methods and schemes for industrial relations dispute resolution (PPHI) in order to improve the productivity of the labor law system in Indonesia. Unresolved industrial relations issues can negatively impact employment stability and national productivity. This study uses a qualitative approach with juridical-normative and juridical-sociological methods to examine laws and regulations and dispute resolution practices in the field. Data were collected through literature studies and interviews with legal practitioners, employers, and labor unions. The results indicate that an ideal PPHI scheme should be fast, fair, affordable, and easily accessible to the parties. In addition, increasing the capacity of dispute resolution institutions, such as mediation at the Manpower Office and arbitration institutions, significantly influences the effectiveness of labor law. Therefore, comprehensive improvements to the PPHI system are essential to create harmonious and productive industrial relations.